Enhanced gas separation properties of metal organic frameworks/polyetherimide mixed matrix membranes. Issue 17 (16th April 2014) - Duan, Cuijia; Kang, Guodong; Liu, Dandan; Wang, Lina; Jiang, Can; Cao, Yiming; Yuan, Quan
ABSTRACT Metal organic frameworks (MOFs) are supposed to be ideal additives for mixed matrix membranes (MMMs). In this article one kind of MOFs, Cu3(BTC)2, is synthesized, then directly incorporated into a model polymer (Ultem®1000) using N, N‐dimethylacetamide as solvent. Cu3(BTC)2 particles are uniformly dispersed and there are no interfacial defects in the prepared MMMs when Cu3(BTC)2 loading is not more than 35 wt %, seen in SEM images. Pure gas permeation tests show that gas permeability increases obviously with Cu3(BTC)2 loading increase, while ideal selectivities of CO2/N2 and CO2/CH4 are almost unchanged. For MMM with the best separation property, CO2 permeability increases about 2.6 times and CO2/N2 selectivity remains almost unchanged. Results about gas diffusivity and solubility indicate that gas diffusivity and solubility make contribution to gas permeability increase at the same time but in different ways. Gas permeation properties of MMMs are well predicted by Maxwell or Bruggeman model. © 2014 The Authors Journal of Applied Polymer Science Published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40719.